PENERAPAN GO DIGITAL MARKETING RESTORAN DALAM UPAYA PENINGKATAN TEKNOLOGI INFORMASI UNIT BISNIS - Linna Ismawati; Raeni Dwi Santy; Angga Setiadi (Jurnal Pengabdian Kepada Masyarakat, 2023)
During the Covid-19 pandemic, the growth of MSMEs in Indonesia went through various challenges, one of which was to encourage changes in consumption patterns of digitally transformed goods and services from marketing conventions to digital marketing. The purpose of carrying out community service activities at Saung Pondok Barokah Umat (SPBU) is to provide assistance while finding several alternative solutions to solving problems experienced by gas stations in managing their business. The method for implementing this activity is field observation at gas stations and socialization of activities with meetings between Proposers and Partners. The results of the research from this community service activity are that it is hoped that managers and students of the Gas Station Business Unit will be able to improve Information Technology capabilities in managing Websites and Social Media as a means to introduce products from these Partners. This activity has participated in helping the program improve the quality of human resources by providing training and coaching on digital marketing and social media applications to support the development of the SPBU Business Unit. It is hoped that managers and students of the Gas Station Business Unit can increase their understanding and ability to develop their business with a market share not only in Islamic boarding schools but reaching a wider area. Keywords: ; ; ; ; Finance; Marketing